Step by Step Construction of Multifunctional Hollow Double Shell MNPs@MOF as a Powerful Tandem/Cascade Catalyst - Shi, Shunli; Yu, Ying; Zhang, Bingzhen; Zhong, Yicheng; Wang, Lei; Wang, Shuhua; Ding, Shunmin; Chen, Chao (Frontiers in Chemistry, 2021)
The development of efficient heterogeneous catalysts for one-pot tandem/cascade synthesis of imines remains meaningful and challenging. Herein, we constructed an Au/MOF catalyst featured hollow and double MOF shell nanostructure. Owing to its structural merits and acid-basic nature, the as-synthesized Void|(Au)ZIF-8|ZIF-8 catalyst exhibited an enhanced synergistically catalytic performance for tandem catalytic synthesis of imines from benzyl alcohol and aniline under air atmosphere and solvent-free condition. Its 170.16 h-1 of turnover frequency (TOF) was 2.5 times higher than that of the reported catalyst with the highest TOF value.